Epigenome Mapping in Quiescent Cells Reveals a Key Role for H3K4me3 in Regulation of RNA Polymerase II Activity - Shengyuan Zeng; Karl Ekwall (Epigenomes)
(1) Background: Quiescent cells are those that have stopped dividing and show strongly reduced levels of gene expression during dormancy. In response to appropriate signals, the cells can wake up and start growing again. Many histone modifications are regulated in quiescence, but their exact functions remain to be determined. (2) Methods: Here, we map the different histone modifications, H3K4me3, H3K9ac, H3K9me2, and H3K9me3, and the histone variant H2A.Z, comparing vegetative and quiescent fission yeast (S. pombe) cells. We also map histone H3 as a control and RNA polymerase II (phosphorylated at S2 and S5) to enable comparisons of their occupancies within genes. We use ChIP-seq methodology and several different bioinformatics tools. (3) Results: The histone modification mapping data show that H3K4me3 changes stand out as being the most significant. Changes in occupancy of histone variant H2A.Z were also significant, consistent with earlier studies. Regarding gene expression changes in quiescence, we found that changes in mRNA levels were associated with changes in occupancy of RNA polymerase II (S2 and S5). Analysis of quiescence genes showed that increased H3K4me3 levels and RNA polymerase II occupancy were super-significant in a small set of core quiescence genes that are continuously upregulated during dormancy. We demonstrate that several of these genes were require Set1C/COMPASS activity for their strong induction during quiescence. (4) Conclusions: Our results imply that regulation of gene expression in quiescent cells involves epigenome changes with a key role for H3K4me3 in regulation of RNA polymerase II activity, and that different gene activation mechanisms control early and core quiescence genes. Thus, our data give further insights into important epigenome changes in quiescence using fission yeast as an experimental model.